Reduced carbon uptake during the 2010 Northern Hemisphere summer from GOSAT. Issue 10 (30th May 2013) - Guerlet, S.; Basu, S.; Butz, A.; Krol, M.; Hahne, P.; Houweling, S.; Hasekamp, O. P.; Aben, I.
<x xml:space="preserve">Abstract</x> [1] Column‐averaged dry air mole fractions of carbon dioxide (XCO2) measured by the Greenhouse Gases Observing Satellite (GOSAT) reveal significant interannual variation (IAV) of CO2uptake during the Northern Hemisphere summer between 2009 and 2010. The XCO2drawdown in 2010 is shallower than in 2009 by 2.4 ppm and 3.0 ppm over North America and Eurasia, respectively. Reduced carbon uptake in the summer of 2010 is most likely due to the heat wave in Eurasia driving biospheric fluxes and fire emissions. A joint inversion of GOSAT and surface data estimates an integrated biospheric and fire emission anomaly in April–September of 0.89 ±0.20 PgC over Eurasia. In contrast, inversions of surface measurements alone fail to replicate the observed XCO2IAV and underestimate emission IAV over Eurasia. This shows the value of GOSAT XCO2in constraining the response of land‐atmosphere exchange of CO2 to climate events.